The role of emotional intelligence in music performance anxiety - Jansen van Rensburg, Magdalena Petronella (University of the Free State, 2005)
The aim of this article is to provide a theoretical frame of reference for Music Performance Anxiety (MPA) and Emotional Intelligence (EI) through an investigation of existing theories concerning the two constructs. The most prominent approaches to the development of MPA are discussed, followed by the different theories concerning EI. Tangential points between MPA and EI are then highlighted. The article is underpinned by the hypothesis that EI is a cognitive-positive way of processing emotions and that it can be used to the advantage of musicians. While the progress of the EI paradigm has been impressive, much remains to be explored.
Dissertation (M.Mus. (Music))--University of the Free State, 2005
Keywords: Music -- Emotions; Music -- Performance -- Psychological aspects; Anxiety -- Psychological aspects; Emotional intelligence; Spielberger State-Trait Anxiety; Empirical study; Relationship; Music perfomance anxiety